Pengaruh CEO Overconfidence Terhadap Manajemen Laba Riil Dengan Kualitas Audit Sebagai Pemoderasi (Studi Pada Sub Sektor Industri Dasar Dan Kimia Tahun 2015-2018) - Isna Putri Rahmawati; Clara Nurcahyani (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2020)
The purpose of this study is to test empirically the effect of CEO overconfidence to real earning management with audit quality as a moderating factor. The sample of this study are basic industrial and chemical sub sector in Indonesia which listing in BEI with a four year period of 2015-2018 totaling 127 observations. This study used multiple linear regression analysis. The test results states that CEO overconfidence does have affect real earning management. While audit quality is proven to weaken the relationship between CEO overconfidence and real earning management. The control variables used in this study are size and free cash flow. The result of the study indicate that size has no effect and free cash flow has effect on real earning management in basic industrial and chemical sub sector.